2019
DOI: 10.1016/j.earlhumdev.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Association between prenatal opioid exposure, neonatal opioid withdrawal syndrome, and neurodevelopmental and behavioral outcomes at 5–8 months of age

Abstract: Background: While use of prescription opioids and medication assisted therapy (MAT) for opioid use disorder in pregnancy, as well as the prevalence of neonatal opioid withdrawal syndrome (NOWS) continue to rise, little is known about outcomes for children with NOWS beyond the newborn period. Methods: We examined 1) prenatal MAT exposure vs. unexposed healthy controls [HC]; and 2) treatment for NOWS and NOWS severity on infant neurodevelopmental and behavioral outcomes at 5–8 months of age in 78 maternal-infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
1
32
0
3
Order By: Relevance
“…Adolescent children prenatally exposed to opioids may exhibit lasting somatosensory deficits (Kivistö et al, 2015) that may be independent of the expression of NOWS (Bakhireva et al, 2019). Adaptation, the cessation of a paw withdrawal response, to repeated stimuli is a key measure of sensory processing.…”
Section: Impaired Sensory Adaptation In Adolescent Micementioning
confidence: 99%
“…Adolescent children prenatally exposed to opioids may exhibit lasting somatosensory deficits (Kivistö et al, 2015) that may be independent of the expression of NOWS (Bakhireva et al, 2019). Adaptation, the cessation of a paw withdrawal response, to repeated stimuli is a key measure of sensory processing.…”
Section: Impaired Sensory Adaptation In Adolescent Micementioning
confidence: 99%
“…However, compared with healthy controls, a higher proportion of neonates born to mothers on MAT had negative affect and self-regulation, and fewer demonstrated typical performance in the sensation-seeking scale. 46 Beckwith and Burke 42 compared 28 infants with in utero opioid exposure with a historical control and found significant differences in the Bayley Scales of Infant and Toddler Development, Third Edition cognitive, language, and motor subscales. The authors of another study examined the outcomes of children whose mothers had received methadone and buprenorphine in pregnancy and found that at 36 months, the children were within normal range on multiple instruments in cognition, sensory processing, and behavior, although there was no control group.…”
Section: Motor and Cognitive Developmentmentioning
confidence: 99%
“…Very few studies have assessed for behavioral outcomes in NOWS infants. In a cohort of 5–8 month olds, Bakhireva et al (2019) reported higher negative affect and lower self-regulation in NOWS infants versus healthy controls. NOWS infants were also more likely to be rated as ‘sensation seeking’, i.e., are more likely to search for additional sensory stimulation via oral (biting/mouthing) or physical (touching) means.…”
Section: Clinical Studies On Perinatal Opioid Exposurementioning
confidence: 89%